2005
DOI: 10.1007/s00216-005-0018-5
|View full text |Cite
|
Sign up to set email alerts
|

Validated HPLC–MS–MS method for determination of azithromycin in human plasma

Abstract: A validated, highly sensitive, and selective HPLC method with MS-MS detection has been developed for quantitative determination of azithromycin (AZI) in human Na2EDTA plasma. Roxithromycin (ROX) was used as internal standard. Human plasma containing AZI and internal standard was ultrafiltered through Centrifree Micropartition devices and the concentration of AZI was determined by isocratic HPLC-MS-MS. Multiple reaction monitoring mode (MRM) was used for MS-MS detection. The calibration plot was linear in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 17 publications
0
36
1
Order By: Relevance
“…The blood samples were centrifuged, and the plasma was aspirated and frozen at Ϫ80°C. The levels of azithromycin in plasma were measured using a validated high-performance liquid chromatography-tandem mass spectroscopy (HPLC/MS/MS) detection method (18). The lower limit of detection was 10 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…The blood samples were centrifuged, and the plasma was aspirated and frozen at Ϫ80°C. The levels of azithromycin in plasma were measured using a validated high-performance liquid chromatography-tandem mass spectroscopy (HPLC/MS/MS) detection method (18). The lower limit of detection was 10 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al (2006) extracted analyte with methyl tert-butyl ether-hexane (50:50 v/v) and monitored [M + 2H] 2+ by liquid chromatography/mass spectrometry (LC/MS). Barrett et al (2005) used an ultrafilter to pretreat sample and Nirogi et al (2005) used solid-phase extraction to prepare plasma, analysis being performed by liquid chromatography/tandem mass spectrometry (LC/MS/MS). All employed complicated and time-consuming sample preparation methods.…”
Section: Azithromycinmentioning
confidence: 99%
“…It was found that a mixture of 50 mM ammonium acetate buffer-acetonitrile could achieve this purpose and was finally adopted as the mobile phase. This binary mobile phase is simpler than those reported in the literatures [23][24][25], which contained methanol, acetonitrile and buffer or with addition of formic acid [26]. It is similar to the mobile phase reported by Abuin et al [27] for the analysis of macrolide antibiotics in river water except for a different concentration of ammonium acetate.…”
Section: Chromatography and Mass Spectrometrymentioning
confidence: 90%
“…Both azithromycin and roxithromycin were rapidly eluted with retention times less than 1.5 min, and the total run time was 3.0 min per sample. The analysis time for azithromycin in the literatures [23,25,27] which used HPLC-MS and HPLC-MS/MS were about 5 min, 6 min and 4 min, respectively. The short analysis time may meet the requirement for high sample throughput in bioanalysis.…”
Section: Chromatography and Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation